2015
DOI: 10.1097/md.0000000000001474
|View full text |Cite|
|
Sign up to set email alerts
|

Modified IDSA/ATS Minor Criteria for Severe Community-Acquired Pneumonia Best Predicted Mortality

Abstract: It is not clear whether the IDSA/ATS minor criteria for severe community-acquired pneumonia (CAP) could be simplified or even be modified to orchestrate improvements in predicting mortality.A retrospective cohort study of 1230 CAP patients was performed to simplify and to modify the scoring system by excluding 4 noncontributory or infrequent variables (leukopenia, hypothermia, hypotension, and thrombocytopenia) and by excluding these variables and then adding age ≥65 years, respectively. The simplification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…We excluded hospitalized patients with suspected SARS-CoV-2 infection but without laboratory confirmation, or patients who did not require hospitalization, with or without laboratory diagnosis of SARS-CoV-2 infection. Thirty-four patients required transfer to the Intensive Care Unit based on the attending specialist’s criteria, and taking into account the CURB65 scale and the ATS/IDSA criteria [16,17]. This study was approved by the Ethics Committee of our Institution (Resolution CEIM 040/2018, amended on 16 April 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We excluded hospitalized patients with suspected SARS-CoV-2 infection but without laboratory confirmation, or patients who did not require hospitalization, with or without laboratory diagnosis of SARS-CoV-2 infection. Thirty-four patients required transfer to the Intensive Care Unit based on the attending specialist’s criteria, and taking into account the CURB65 scale and the ATS/IDSA criteria [16,17]. This study was approved by the Ethics Committee of our Institution (Resolution CEIM 040/2018, amended on 16 April 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For the IDSA/ATS guideline, only the minor criteria were assessed (threshold ≥3), as the major criteria (mechanical ventilation and vasopressor support) would normally present a clear indication for ICU admission. This approach has been adopted previously . Diagnostic accuracy of the lowest severity class for each score was then assessed for prediction of discharge within 48 h. These thresholds were PSI class I, CURXO score ≤4 (no major or minor criteria), no major or minor IDSA/ATS criteria and a score of zero points for CURB‐65, CORB and SMARTCOP.…”
Section: Methodsmentioning
confidence: 99%
“…A validation study of 1062 patients with CAP, not meeting the major criteria, found the minor criteria were equivalent to the SMART-COP scoring system for predicting need for mechanical ventilation, vasopressor support, and ICU care [59]. Recently, other investigators have modified the IDSA/ATS minor criteria by excluding four infrequent variables [leucopenia, hypothermia, hypotension, and thrombocytopenia] but adding age ≥65 years [60]. The modified version best-predicted mortality, but it is unclear whether it is as useful for predicting need for ICU care and vasopressor/ventilation support.…”
Section: Markers Of Prognosis Of Capmentioning
confidence: 99%